Study on the spatiotemporal regulation of interferon-stimulated genes during Zika virus infection - Chen, Xiao Zhong; Gong, Yuan Xin; Guo, Hong Xia; He, Jiu Xiang; Yang, TongYan; Li, Jin Tao (Frontiers in Immunology, 2026)
BackgroundZika virus (ZIKV) can cause severe neurological disorders such as congenital microcephaly, and there are currently no approved prevention or treatment measures. Elucidating the antiviral mechanism of the host interferon-stimulated genes (ISGs) is crucial for the development of therapeutic strategies.MethodsThis study integrated multisystem transcriptomic data [human brain organoids, monocyte-derived dendritic cells (moDCs), and peripheral blood mononuclear cells (PBMCs) from infected patients], combined with cellular experiments and bioinformatics analysis, to systematically investigate the spatiotemporal regulation characteristics and functions of ISGs during ZIKV infection.ResultsThe results showed that treatment with interferon beta (IFN-β) significantly activated the ISGs (e.g., IRF7 and IFITM3) in the ZIKV-infected brain organoids, which were enriched in virus defense-related pathways. Single-cell transcriptomics revealed cellular heterogeneity in the IFN-β-driven ISG responses in moDCs. Transcriptomic analysis of the PBMCs identified 210 differentially expressed genes between the acute and convalescent phases. Core ISGs (e.g., RSAD2 and OAS3) were transiently upregulated in the acute phase. Through cross-analysis, 22 cross-system shared ISGs were screened out. Least absolute shrinkage and selection operator (LASSO) regression identified 11 potential diagnostic biomarkers for ZIKV infection. Small interfering RNA (siRNA) knockdown experiments confirmed that IFI35, IFI44, and OAS3 exerted antiviral effects by inhibiting ZIKV replication.ConclusionThis study reveals the functional plasticity of ISGs and provides key targets and theoretical support for the prevention and treatment of ZIKV.